2021
DOI: 10.1002/pd.5939
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic potential of targeted imaging of the fetal pancreas

Abstract: Objective: To report our experience with targeted scans of the fetal pancreas.Methods: Targeted scans were performed in 16 cases referred for anatomical or genetic conditions associated with structural pancreatic malformations.Results: Four fetuses were evaluated for nephromegaly and macroglossia. In three of them, the pancreas circumference was >90th percentile. Genetic testing revealed Beckwith-Wiedemann syndrome. In the fourth case, the pancreas circumference was normal; exome sequencing revealed two hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Visualization was conducted in R. The gene expression matrix, enrichment plots and differential expression boxplot were depicted by "ggplot2" R package [22]. The venn diagram was drawn with "VennDiagram" R package [23].…”
Section: Data Visualizationmentioning
confidence: 99%
“…Visualization was conducted in R. The gene expression matrix, enrichment plots and differential expression boxplot were depicted by "ggplot2" R package [22]. The venn diagram was drawn with "VennDiagram" R package [23].…”
Section: Data Visualizationmentioning
confidence: 99%
“…Other findings such as characteristics of the omphaloceles themselves (smaller, containing bowel only), large placenta, and specific organomegalies should also raise suspicion for BWS and trigger genetic counseling and targeted molecular testing. 2 Four reports in this issue, [3][4][5][6] BWS can be caused by different molecular mechanisms 2,7 and the contributions of each are mostly derived from postnatal or combined postnatal and prenatal testing data. Those showed that the most common cause is loss of methylation of imprinting control region 2 (IC2) on the maternally inherited chromosome in 50%, uniparental paternal disomy of chromosome 11 in 20% which can be mosaic, gain of methylation of imprinting control region 1 (IC1) on the maternally inherited chromosome in 5%, or heterozygous deletions of 11p15.5 in about 2%.…”
mentioning
confidence: 99%
“…Gilboa et al 4 pay particular attention to measurements of the circumference of the fetal pancreas. In four cases referred for nephromegaly and macroglossia, that also had elevated human chorionic gonadotropin on maternal serum screen, the three with an enlarged pancreas were confirmed to have BWS while the fourth, with a normally sized pancreas, was diagnosed with a different condition.…”
mentioning
confidence: 99%
See 2 more Smart Citations